Achieving high-quality care: a view from NICE. Issue 1 (14th September 2017) - Leng, Gillian; Partridge, Gemma
Abstract : The National Institute for Health and Care Excellence (NICE) was established in 1999 to provide evidence-based guidance. The task of producing guidance by reviewing primary research data and using an advisory committee to develop evidence-based recommendations, is not straightforward. Guidance production is, however, less challenging than the task of putting evidence-based recommendations into practice. NICE is very sensitive to this challenge as, since 1999, over 1500 pieces of NICE guidance have been published. A number of pieces of guidance relate to heart disease, including pharmaceutical agents, new medical technologies and clinical guidelines. Examples include guidelines on acute heart failure and atrial fibrillation, and advice on technologies including edoxaban and implantable cardioverter defibrillators. The research evidence is clear that a change in practice rarely comes about as a result of simply disseminating guidance on best practice. Simple dissemination is particularly ineffective if the guidance has not been produced by a well-respected, credible organisation. It is also clear from the literature that implementation is more successful when more than one approach is taken, and when there is alignment between efforts at organisational, local and national levels. At an organisational level, there should be support from the Board for quality improvement, with ongoing measurement of progress. Resources should be provided for targeted change programmes, particularly where new guidance suggests improvements are required. A systematic process for putting change in place should include identifying barriers to change, agreeing interventions to overcome the barriers and drive forward improvement and planning for implementation and evaluation.